Phase map analysis using axial behavior of reconstructed wavefronts - Maallo, Anne Margarette Santos
A novel fringe processing algorithm for the spatial evaluation of optical wavefronts is proposed. The generic algorithm is applicable to wavefronts obtained from any reconstruction method be it interferometric (e.g., holography) or non-interferometric (e.g., phase retrieval). A numerically reconstructed wavefront is first propagated to different axial positions where the phase maps are plotted. The phase maps are then processed using the proposed statistical algorithm. The algorithm calculates the axial contrasts of the standard deviation values inside small windows in each of the phase maps. The output of the algorithm is a contrast map that can be used to characterize spatial features in the wavefront. Time complexity analysis of the worst case problem shows that the algorithm has linear time.